Ab initio study of absorption resonance correlations between nanotubes and nanoribbons of graphene and hexagonal boron nitride - Payod, Renebeth B. (Animo Repository, 2019)
Density functional theory calculations are performed for the electronic band structures and optical absorption spectra of the zigzag nanoribbons and armchair nanotubes of graphene and hexagonal boron nitride as well as hybrid tubular structures obtained by embedding two dimer lines of B and N atoms into an armchair nanotube. Linear correlation coefficient analysis is carried out to quantitatively investigate relations between energies of absorption resonances in these tube-ribbon pairs. Despite the large disparity in the energy band gaps of some of these structures, our results show a high degree of correlation (r > 0.85 with >95% confidence level) between them.